Two-phase SLIPI for instantaneous LIF and Mie imaging of transient fuel sprays - Storch, Michael; Mishra, Yogeshwar Nath; Kögl, Matthias; Kristensson, Elias; Zigan, Lars; Berrocal, Edouard; Will, Stefan (Optics Letters, 2016)
We report in this Letter a two-phase structured laser illumination planar imaging [two-pulse SLIPI (2p-SLIPI)] optical setup where the "lines structure" is spatially shifted by exploiting the birefringence property of a calcite crystal. By using this optical component and two cross-polarized laser pulses, the shift of the modulated pattern is not "timelimited" anymore. Consequently, two sub-images with spatially mismatched phases can be recorded within a few hundred of nanoseconds only, freezing the motion of the illuminated transient flow. In comparison with previous setups for instantaneous imaging based on structured illumination, the current optical design presents the advantage of having a single optical path, greatly simplifying its complexity. Due to its virtue of suppressing the effects from multiple light scattering, the 2p-SLIPI technique is applied here in an optically dense multi-jet direct-injection spark-ignition (DISI) ethanol spray. The fast formation of polydispersed droplets and appearance of voids after fuel injection are investigated by simultaneous detection of Mie scattering and liquid laser-induced fluorescence. The results allow for significantly improved analysis of the spray structure. (C) 2016 Optical Society of America